1998
DOI: 10.1093/hmg/7.9.1431
|View full text |Cite
|
Sign up to set email alerts
|

Association between uncoupling protein polymorphisms (UCP2-UCP3) and energy metabolism/obesity in Pima indians

Abstract: The UCP2-UCP3 gene cluster maps to chromosome 11q13 in humans, and polymorphisms in these genes may contribute to obesity through effects on energy metabolism. DNA sequencing of UCP2 and UCP3 revealed three polymorphisms informative for association studies: an Ala-->Val substitution in exon 4 of UCP2, a 45 bp insertion/deletion in the 3'-untranslated region of exon 8 of UCP2 and a C-->T silent polymorphism in exon 3 of UCP3. Initially, 82 young (mean age = 30 +/- 7 years), unrelated, full-blooded, non-diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
206
3
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(226 citation statements)
references
References 19 publications
11
206
3
6
Order By: Relevance
“…In humans, some, but not all (Klannemark et al 1998), studies showed that UCP2 gene variants are implicated in diabetes, obesity, and fat metabolism (Zhang et al 2001) and are strongly linked to resting energy expenditure (Astrup et al 1999;Buemann et al 2001;Walder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, some, but not all (Klannemark et al 1998), studies showed that UCP2 gene variants are implicated in diabetes, obesity, and fat metabolism (Zhang et al 2001) and are strongly linked to resting energy expenditure (Astrup et al 1999;Buemann et al 2001;Walder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, VV genotype, in comparison to those who have the AA or A/V genotype, have a lower degree of uncoupling, lower energy expenditure (Astrup et al 1999), higher exercise energy efficiency (Buemann et al 2001), and lower fat oxidation. However, it has been reported that persons with the I/D genotype have an increased basal metabolic rate, increased 24-h energy expenditure and decreased BMI (Esterbauer et al 2001), as well as a low deposition index (Walder et al 1998).Recently, the −866 G-allele has been described to influence UCP2 transcription, to be associated with reduced adipose tissue mRNA expression, reduced transcriptional activity in vitro and in vivo, high BMI, fat mass changes (Yoon et al 2007), increased risk of obesity (Esterbauer et al 2001;Argyropoulos and Harper 2002;Vogler et al 2005), increased insulin response to glucose and reduced risk of T2D (Krempler et al 2002;Esterbauer et al 2001;Sesti et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…G (À 3862) polymorphism in the promoter of the UCP1 gene has been associated with increased BMI (Hayakawa et al, 1999;Heilbronn et al, 2000) whereas other studies have failed to demonstrate any association between obesity and this UCP1 polymorphism (Gagnon et al, 1998;Urhammer et al, 1997). The I/D variant of UCP2 in the 3 0 untranslated region of exon 8 of UCP2 was found to be associated with increased sleeping metabolic rate and 24-h energy expenditure and with lower BMI in Pima Indians (Walder et al, 1998), and homozygous carriers of the insertion had increased BMI in a South Indian population (Cassell et al, 1999). The T allele in UCP3 C !…”
Section: Discussionmentioning
confidence: 90%
“…12 In a population-based sample from the same geographic area, a common UCP2 polymorphism could account for 15% of the obesity prevalence, 12 and genetic variation at the UCP2 locus is associated with energy expenditure in Pima Indians. 21 Together, these observations suggest a role for UCP2 in obesity by influencing energy metabolism although a specific uncoupling function has not been confirmed in humans. 10 In addition, UCP2 is at least in part regulated through PPARg as PPARg agonists increases adipose UCP2 expression.…”
Section: Overfeeding and Pparc Activity Amcp Joosen Et Almentioning
confidence: 94%
“…The study enclosed a 7-day baseline period (days 1-8) and a 14-day overfeeding period (days [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. During the baseline period subjects chose their diets from a variety of food items provided daily in weighed food packages, bringing back the leftovers the next day, for calculation of habitual energy intake.…”
Section: Experimental Designmentioning
confidence: 99%